Malabsorption of Vitamin B12 in Homozygous ß-Thalassemia - Vlachos, P.; Liakakos, D. (Nuklearmedizin - NuclearMedicine, 1976)
Schilling tests were performed in ten children aged 5—12 years suffering from homozygous β-thalass-emia. 57Co labelled vitamin B12 values excreted in the urine have been found much lower than normal and remained low when the same procedure was repeated with the addition of intrinsic factor. The possible factors responsible for this malabsorption of vitamin B12 seemed to be liver damage and folic acid deficiency.